DELIVERY TRACKING SYSTEM WITH ON-DEMAND LOCATION UPDATE DI PT ANUGRAH HADI ELECTRIC MENGGUNAKAN METODE AGILE - Anggi Irawan; Aditya Satya Laksana; Wasis Haryono (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2024)
PT Anugrah Hadi Electric, an electrical general supplier in Tangerang, faces challenges in the process of delivering goods to customers in the Jabodetabek area. The company still relies on conventional delivery methods where the owner directly delivers the goods, which causes constraints in time efficiency and communication with customers. This research aims to develop a delivery tracking system with on-demand location update feature to improve operational efficiency and customer satisfaction. Using Agile methodology, the system is developed by integrating Firebase technology for real-time location tracking, Kotlin for mobile application development, Laravel as the backend framework, and MySQL as the database. The system allows customers to monitor delivery status directly through the application, reducing the need for manual communication with the owner. The implementation results show significant improvements in delivery efficiency and customer satisfaction. The system successfully reduces the communication burden on the owner and provides better transparency to customers regarding the status of their shipments. For further development, the addition of automatic notification features, improved data security, and integration with digital payment systems are recommended. Periodic evaluation of the application's performance is also needed to ensure the system continues to meet the needs of the company and customers along with technological developments.